I You He She It experiments in Viewpoint - Stewart, Michael (University of Huddersfield Press, 2017)
The latest Grist Anthology is an innovative blend of some of the most exciting and freshest voices in prose and poetry today. It features five sections written from five distinct narrative viewpoints.